Thyroid function as assessed by routine laboratory tests of workers with long-term lead exposure. - Tuppurainen, M; Wagar, G; Kurppa, Kari; Sakari, W; Wambugu, A; Froseth, B; Alho, J; Nykyri, E (Scandinavian Journal of Work, Environment & Health, 1988)
Thyroid function was studied in 176 male workers occupationally exposed to lead. The mean blood lead concentration of the workers was 2.70 (SD 1.15, range 0.70-6.45) mumol/l. The mean duration of lead exposure was 7.6 (range 0.1-20) years. The total thyroxine (T4), free thyroxine (FT4), total triiodothyronine (T3), and thyrotropin concentrations in serum were similar in the workers in the low and high blood lead categories. In regression equations the duration of lead exposure had a weak but significant negative association with T4 and FT4, and this association was particularly pronounced when the analyses were restricted to workers with the most intense lead exposure over time. Thus, the results suggest that thyroid function might be depressed as a result of intense long-term lead exposure.